Why Mars And Venus Collide - John Gray
Once upon a time, Martians and Venusians functioned in separate worlds. But in today's hectic and career-oriented environment, relationships have become a lot more complicated, and men and women are experiencing unprecedented levels of stress. To add to the increasing tension, most men and women are also completely unaware that they are actually hardwired to react differently to the stress. It's a common scenario: a husband returns home from work stressed out and eager to kick back on the couch and watch television. A wife returns home from work stressed out and wants to talk about it with her husband. What happens? Neither is on the same page, anger and resentment set in, and Mars and Venus collide.